SISTEM PENDUKUNG KEPUTUSANDALAM PEMILIHAN SUPPLIER KEMASAN (BOX PACKAGING) TERBAIK DENGAN METODE FUZZY ANALYTHICAL HIERARCHY PROCESS (Studi Kasus Pada CV. BANYOE ATIKA MANDIRI) - Sudaryono Sudaryono; Najmuddin Najmuddin (Jurnal Ilmiah Sains dan Teknologi, 2018)
ABSTRACT The availability of packaging used to support the business process that is being carried out will depend on the selection of the best suppliers. Determine suppliers by applying the Multi Criteria Decision Making method based on predetermined criteria such as price, shipping, warranty and complaints service, and quality. The addition of fuzzy logic in the Analytical Hierarchy Process method is used to enhance the accuracy of the subjectivity of the assessment so that in this study the method of Fuzzy Analytical Hierarchy Process is used. The results of the Fuzzy Analytical Hierarchy Process method are obtained as follows: PT. Cakrawala Mega Indah with a value of 0.754, PT. Uniflex Kemasindo with a value of 0.639, PT. Starindo with a value of 0.636, and PT. Unipack Indosystem with a value of 0.154.